Factors Affecting the Successful Debt Collection Legal Services Business in Thailand - Chanpanyalert, Kanpisit; Leecharoen, Benjawan; Sangthong, Thaunjai (Journal of Rattana Bundit University, 2025)
This article aimed to present the factors effecting the successful debt collection service businesses in Thailand. The literature review method on the successful debt collection service businesses provided knowledge about their successes in Thailand using the Balanced Scorecard concept as a tool to measure organizational successes for four perspectives: financial, customer, internal process, and learning and development. The results indicated that the factors effecting the successful debt collection service businesses included 4 factors: organizational management, customer relationship management, entrepreneur characteristics, and organizational credibility. It was recommended that synthesis of the content with the model factors effecting the successes of debt collection service businesses in Thailand for organizational executives. They could understand the key factors leading to successful business and effective application.